Vaccine-preventable diseases screening and vaccination programs for healthcare professions students. (30th September 2020) - Letzgus, M; De Nard, F; Gaiazzi, M; Rivolta, S; Grimoldi, L; Magnoni, P; Gervasi, F; Carrer, P; Castaldi, S
Abstract: Background: Students in Healthcare Professions (SHPs) present an increased risk of contracting and transmitting Vaccine-Preventable Diseases (VPDs). Our study aimed to investigate the organizational strategies (screening and immunization for VPDs and vaccination promotion among SHPs) implemented by the healthcare facilities accredited with the University of Milan. Methods: we sent an e-survey by e-mail to medical residents and first- and last-year students in nursing, midwifery and healthcare assistance. Results: among 3397 invited SHPs, 645 participated. We included in the analysis 522 SHPs, distributed in 24 facilities across the Lombardy region (mean age 27, 4 years; 69, 5% female; 69% medical residents, 28% nursing, 2% healthcare assistance, and 1% midwifery students). Although most participants underwent occupational health visit before the traineeship start (47, 5%) or within 6 months (29, 5%), others hadn't undergone yet (15, 1%). The visits included the collection of vaccination history (72, 6%; 64, 6% from written documentation), serological tests for VPDs (hepatitis B 76, 1%, measles and rubella 58, 4%, varicella 54, 4%), and screening for latent TB (69, 7%). Vaccinations were recommended to 226 participants, but only 173 fully (76, 5%) or partially (8%) complied. Full compliance was associated with nudges like in-hospital (Chisq. 18, 7; p = 0.00) and free vaccinations (Chisq. 31; p = 0.00). Reported facility vaccination policies included campaigns (posters 37, 4%, intranet 39, 5%, social media 11, 5%, general/personalized letters 30, 3%/11, 5%), time-off incentives (7, 7%), on-site (30, 5%) and opinion leaders' vaccinations (9, 8%). However, SHPs were often unaware of those strategies (mean 48, 6%), and intra-facility answers were sometimes discordant (agreement <70% for facilities with >30 respondents). Conclusions: SHPs are often unaware or discordant regarding vaccination policies carried out by traineeship facilities, suggesting the need of inclusive communication strategies. Key messages: About half of students in healthcare professions are screened for VPDs after the start of the traineeship. Students in healthcare professions are often unaware of vaccination promotion strategies.